DIPLOMASI AUSTRALIA DALAM BIDANG PENDIDIKAN DI INDONESIA TAHUN 2014-2021 - Jihan Nadira Eminita G.; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Diplomatic efforts in the field of education are needed to build education for the entire community in order to create a fair and equitable quality education system. Australia conducts diplomacy in the field of education in Indonesia to promote its national interests, and considering the condition of education in Indonesia which is still experiencing many problems, such as the lack of availability of education funds, the low quality of teaching staff, and the unavailability of adequate facilities. The cooperation between Australia and Indonesia in the field of education is supported by the MoU which includes cooperation at all levels of education. In this case, this study will discuss Australia's diplomatic efforts in the field of education in Indonesia.          The analysis in this study is based on the theory of Multi track Diplomacy which implements diplomacy in education through 9 pathways. The perspective used is the perspective of pluralism which argues that the actors in IR are very diverse and the existence of these actors is very influential. So this research will analyze the actors involved in Australian and Indonesian education programs. The level of analysis in this research is the nation-state with a qualitative descriptive research method, where the research is carried out covering the activities of collecting, compiling, and analyzing data. This research is limited to the period 2014-2021.          Australia's diplomatic efforts in the field of education towards Indonesia have been successfully implemented through the channels in Multi Track Diplomacy. Education programs in Indonesia are running well with the presence of various actors, such as the government, professionals, communities, academics, activists, institutions, organizations, and the media who participate in the implementation of educational cooperation between Australia and Indonesia.Keywords: Australia, Indonesia, Multi Track Diplomacy, education